THE RESILIENCE OF TRADITIONAL CULINARY CUISINE OF BENAN ISLAND DEAL THE DOMINANCE OF MODERN FOOD IN MARINE TOURISM AREAS - Rosie Oktavia Puspita Rini; Astika Mutiarazma (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
Benan Island in Lingga Regency possesses a rich coastal Malay gastronomy that serves as a primary attraction for marine tourism. However, tourism development brings challenges such as the penetration of modern food that threatens the existence of local cuisine. This study aims to explore the resilience strategies of Benan Island’s traditional culinary in maintaining authenticity amidst the dominance of industrial food. Using a qualitative-ethnographic approach, data were collected through participatory observation and in-depth interviews with restaurant owners (RM Malong, RM Pa Acay, and RM Mutiah) and sea cucumber farmers. The results indicate that Benan's culinary resilience stems from the sovereignty of local raw materials such as Sagai and Selikur fish, as well as the use of natural acidifiers (mempelam and starfruit). The